2013
DOI: 10.1007/s10508-013-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Depressive Distress by Sexual Orientation in Emerging Adults: The Roles of Attachment and Stress Paradigms

Abstract: Lesbian, gay, and bisexual youth have elevated rates of depression compared to heterosexuals. We proposed and examined a theoretical model to understand whether attachment and stress paradigms explain disparities in depressive distress by sexual orientation, using the longitudinal Growing Up Today Study (GUTS) and Nurses’ Health Study II (NHSII). GUTS participants eligible for this analysis reported sexual orientation, childhood gender nonconforming behaviors (GNBs), attachment to mother (all in 2005), and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 78 publications
4
37
0
Order By: Relevance
“…The item responses have been related to health and other outcomes in expected ways. 9092 Sexual orientation in GUTS was assessed in 1999, 2001, 2003, 2005, 2007, and 2010. We categorized responses into 4 groups: completely or mostly homosexual (LG), bisexual (BI), mostly heterosexual (MH), and completely heterosexual (CH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The item responses have been related to health and other outcomes in expected ways. 9092 Sexual orientation in GUTS was assessed in 1999, 2001, 2003, 2005, 2007, and 2010. We categorized responses into 4 groups: completely or mostly homosexual (LG), bisexual (BI), mostly heterosexual (MH), and completely heterosexual (CH).…”
Section: Methodsmentioning
confidence: 99%
“…We used generalized estimating equations with a working exchangeable assumption in all analyses to adjust for nonindependence introduced by repeated measures on participants or with sibling clusters, 103,104 procedures we have used elsewhere with longitudinal data. 92,105 We performed analyses with SAS 9.3 (SAS Institute Inc, Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
“…Initial evidence concerning sexual orientation disparities in depressive symptoms trajectories comes from the National Longitudinal Study of Adolescent to Adult Health. 9 -11 Using 4 waves of National Longitudinal Study of Adolescent to Adult Health data covering a 13-year period (from wave 1 in 1994-1995 to wave 4 in 2007-2009), trajectory analyses revealed that sexual orientation disparities in depressive symptoms were present as early as adolescence (grades [7][8][9][10][11][12] and persisted into early adulthood (ages 24-32 years), 10 and these disparities were more pronounced among female participants. 11 Trajectory studies using more recent samples revealed conflicting evidence.…”
mentioning
confidence: 99%
“…As earlier studies have shown, the sexual identity of a child can affect the child's relationship with his or her parents. Rosario et al (2014) even pointed out that mothers are less affectionate to their homosexual or bisexual child than the child's heterosexual siblings. Since the RFSL members in the index group were older, maybe their relationships with their parents had less impact on their lives and maybe they lived in an environment that was more tolerant of sexual minorities and this made it easier for them to live their lives.…”
Section: Discussionmentioning
confidence: 99%